2011
DOI: 10.1002/mc.20740
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic polymorphisms in pre‐microRNAs and risk of cervical squamous cell carcinoma

Abstract: MicroRNAs (miRNAs) function as gene regulator and they participate in diverse biological pathways. Common single nucleotide polymorphisms (SNPs) in pre-microRNAs may change their property through altering miRNAs expression and/or maturation. We conducted a pilot study to test whether SNPs in pre-microRNAs were associated with cervical squamous cell carcinoma (CSCC). Genotypes of three SNPs in pre-miRNAs (hsa-miR-196a2 rs11614913 C/T, hsa-miR-499 rs3746444 A/G, and hsa-miR-146a rs2910164 G/C) in 226 CSCC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 32 publications
6
70
1
2
Order By: Relevance
“…These results are in agreement with those reported for breast cancer, since the authors had shown that the variant A > G of miR-499 is associated with a significantly increased risk of developing this cancer, with a 1.75 odd risk [38]. Similarly, the G allele was found to be significantly associated with an increased risk of cervical squamous cell carcinoma [42]. Even if both these two published studies suggested a role for the G allele in determining an increased incidence for respective cancers, no functional connection was previously demonstrated to support the relationship between genotype and cancer risk.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with those reported for breast cancer, since the authors had shown that the variant A > G of miR-499 is associated with a significantly increased risk of developing this cancer, with a 1.75 odd risk [38]. Similarly, the G allele was found to be significantly associated with an increased risk of cervical squamous cell carcinoma [42]. Even if both these two published studies suggested a role for the G allele in determining an increased incidence for respective cancers, no functional connection was previously demonstrated to support the relationship between genotype and cancer risk.…”
Section: Discussionsupporting
confidence: 92%
“…There were fifteen studies of caucasian descent and twenty-four studies of Asian descent. The genotype distributions in the controls of fourteen studies were not conforming to HWE (p<0.05) (Okubo et al, 2010;Akkiz et al, 2011;Ling et al, 2011;Mittal et al, 2011;Zhou et al, 2011;Xiang et al, 2012;Shan et al, 2013;Vinci et al, 2013;Wei et al, 2013;Zou and Zhao, 2013;Bansal et al, 2014;Ma et al, 2014;Omrani et al, 2014;Wang et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…One study was excluded as it was not associated with hsa-mir-499 rs3746444 A>G (Kupcinskas et al, 2012). After further excluding two abstracts (Hu et al, 2009;Hwang et al, 2010), thirty-nine case-control studies involving 14,136 cases and 16,937 controls were selected for meta-analysis (Hu et al, 2009;Tian et al, 2009;Catucci et al, 2010;Liu et al, 2010;Okubo et al, 2010;Srivastava et al, 2010;Akkiz et al, 2011;George et al, 2011;Ling et al, 2011;Mittal et al, 2011;Vinci et al, 2011;Zhou et al, 2011;Alshatwi et al, 2012;Chu et al, 2012;Kim et al, 2012;Min et al, 2012;Xiang et al, 2012;Zhou et al, 2012;Ahn et al, 2013;Lv et al, 2013;Shan et al, 2013;Song et al, 2013;Umar et al, 2013;Vinci et al, 2013;Wei et al, 2013;Wu et al, 2013;Zou and Zhao, 2013;Bansal et al, 2014;Chu et al, 2014;Du et al, 2014;Gutierrez-Camino et al, 2014;Hasani et al, 2014;Hou et al, 2014;Hu et al, 2014;Ma et al, 2014;Omrani et al, 2014;Pu et ...…”
Section: Methodsmentioning
confidence: 99%
“…The study selection process is shown in Figure 1. Finally, 22 articles (Jazdzewski et al, 2008;Xu et al, 2008;Hoffman et al, 2009;Hu et al, 2009;Tian et al, 2009;Catucci et al, 2010;Guo et al, 2010;Liu et al, 2010;Okubo et al, 2010;Pastrello et al, 2010;Srivastava et al, 2010;Xu et al, 2010;Zeng et al, 2010;Garcia et al, 2011;George et al, 2011;Akkiz et al, 2011;Hishida et al, 2011;Mittal et al, 2011;Permuth-Wey et al, 2011;Yue et al, 2011;Zhou et al, 2011;Zhou et al, 2012) with 11,901 cases and 14,200 controls were included in the present meta-analysis. An article by Catucci et al (2010) reported a case-control study of a German population and an Italian population separately, and one by Jazdzewski et al (2008) reported studies on populations of Finland, Poland, and USA separately.…”
Section: Selection Of Studiesmentioning
confidence: 99%